Bolometric Properties of a Spin-Torque Diode Based on a Magnetic Tunnel Junction - G. D. Demin; K. A. Zvezdin; A. F. Popkov (Advances in Condensed Matter Physics)
Spin caloritronics opens up a wide range of potential applications, one of which can be the thermoelectric rectification of a microwave signal by spin-diode structures. The bolometric properties of a spin-torque diode based on a magnetic tunnel junction (MTJ) in the presence of a thermal gradient through a tunnel junction are discussed. Theoretical estimates of the static and dynamic components of the microwave sensitivity of the spin-torque diode, related to thermoelectric tunnel magneto-Seebeck effect and the thermal transfer of spin angular momentum in the MTJ under nonuniform heating, are presented. Despite the fact that the thermal contribution to the microwave sensitivity of the spin-torque diode is found to be relatively small in relation to the rectification effect related to the modulation of the MTJ resistance by a microwave spin-polarized current, nevertheless, the considered bolometric effect can be successfully utilized in some real-world microwave applications.